Simplifying the expression would be 19.76.
Answer:
32 US dollars
Step-by-step explanation:
Explanation
Given a function f(x) we translate the function:
• a units horizontally (a > 0 to the right, a < 0 to the left),
,
• b units vertically (b > 0 up, b < 0 down),
by the transformation:
![f(x)\rightarrow g(x)=f(x-a)+b.](https://tex.z-dn.net/?f=f%28x%29%5Crightarrow%20g%28x%29%3Df%28x-a%29%2Bb.)
In this case, we have:
![\begin{gathered} f(x)=|x|, \\ g(x)=|x-2|+4=f(x-2)+4. \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D%7Cx%7C%2C%20%5C%5C%20g%28x%29%3D%7Cx-2%7C%2B4%3Df%28x-2%29%2B4.%20%5Cend%7Bgathered%7D)
Comparing f(x) and g(x) with the general transformation above, we see that the graph of g(x) is the graph of f(x) translated:
• a = 2 units to the right,
,
• b = 4 units up.
Translating the graph of f(x), we get:
Answer
The translated graph is the graph in red:
Answer:
<h3>12√6</h3>
Step-by-step explanation:
Given the expression;
2√3 * 3√√8
= (2*3) * (√3*√8)
= 6 * (√24)
= 6 * √4*6
= 6 * (2√6)
= (6*2)√6
= 12√6
Hence the simplified form of the expression is 12√6